2022
DOI: 10.1002/iju5.12434
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular large B‐cell lymphoma in renal cell carcinoma incidentally detected by robot‐assisted partial nephrectomy

Abstract: Introduction Intravascular large B‐cell lymphoma is a rare and aggressive type of extranodal large B‐cell lymphoma. Although intravascular large B‐cell lymphoma can invade various organs, renal involvement has been rarely reported. Synchronous occurrence of intravascular lymphoma with renal cell carcinoma is extremely rare. We herein report a case of intravascular large B‐cell lymphoma in a renal cell carcinoma incidentally detected by robot‐assisted partial nephrectomy. Case presentation A 69‐year‐old female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The nervous system and the skin are the most commonly affected areas. IVLBCL has been discovered in a growing number of tissues and organs, including the lungs, 13,14 breast, 15 uteri, 16 prostate, 17 liver, 18 kidneys, 19,20 and thyroid, 21 as awareness of the disease has increased. While this disease is uncommon in the gastrointestinal system, certain research has demonstrated that 8% (3 of 38) of IVLBCL patients manifest in the gastrointestinal system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nervous system and the skin are the most commonly affected areas. IVLBCL has been discovered in a growing number of tissues and organs, including the lungs, 13,14 breast, 15 uteri, 16 prostate, 17 liver, 18 kidneys, 19,20 and thyroid, 21 as awareness of the disease has increased. While this disease is uncommon in the gastrointestinal system, certain research has demonstrated that 8% (3 of 38) of IVLBCL patients manifest in the gastrointestinal system.…”
Section: Discussionmentioning
confidence: 99%
“…The most common sites are the nervous system and skin. However, with the gradual deepening of the understanding of the disease, IVLBCL has been found in an increasing number of tissues and organs, such as the lung [12,13] ,breast [14] ,uterus [15] ,prostate [16] ,liver [17] ,kidney [18,19] , and thyroid [20] . This disease is relatively rare in the gastrointestinal tract, but some studies have found that 8% (3/38) of IVLBCL case appear in the gastrointestinal tract [10] .…”
Section: Decisionmentioning
confidence: 99%